Policy Model of Degraded Land Control in the Anai Watershed West Sumatra Province - Indonesia - Umar, Iswandi; Pratama, Reski (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Increasing population growth has an impact on the need for land, giving rise to conflicts in its utilization. Land use conflicts lead to the growth of degraded land. The aim of this research is to determine the degraded land index and policy directions for controlling degraded land in the Anai watershed. To determine the degraded land index using a GIS approach with four indicators, namely: percentage of land cover, slope, soil depth, and land management. Next, to determine the direction of degraded land control policies using the AHP approach. The research results show that around 48% of the Anai watershed is degraded land. The results of the analysis of the AHP approach to policy strategies in controlling degraded land show that there are three priority directions, namely: 1) increasing community knowledge about forests; 2) increasing community skills regarding the added value of forest products; and 3) strengthening the institutions of indigenous community groups in forest areas. ​